Bridging the gap in hematological malignancies. Issue 3 (June 2012) - Parmar, Simrit; Iyer, Swami Padmanabhan
After the success of the BTG Series in Singapore in 2010 and 2011, meeting organizers held the 3rd International Hematologic Malignancies Conference in Hong Kong. Held on 23–25 February, the BTG meeting provided an opportunity to further scientific discourse in the Asia–Pacific region. Featuring the world-renowned medical faculty and an abundance of discussion forums, the conference provided attendees the opportunity to interact with field leaders and exposed them to the latest research. The BTG conferences focus on hematologic malignancies, especially leukemia, lymphoma and myeloma. The BTG series provides an exceptional platform for the exchange of ideas for the Asia–Pacific hematology oncology healthcare community. It offers many novel opportunities for practicing physicians as well as fellows in training to meet with the world thought leaders. The annual conference brings together key opinion leaders from the Asia–Pacific region, the USA and Europe. The underlying motto is to bring the continents together and generate a global community in the quest against cancer. BTG recognizes the contributions of the Asia–Pacific physicians who are among the world leaders and gives the younger generation opportunities to present their work in a world arena.